2017
DOI: 10.21037/jtd.2017.04.50
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of a right anterolateral minithoracotomy rather than a median sternotomy in isolated tricuspid redo procedures

Abstract: Background:To compare results of tricuspid valve (TV) reoperation between incision via a right anterolateral minithoracotomy (RAMT) and median sternotomy (MS). Methods:We performed a retrospective analysis of 49 patients who underwent isolated TV surgery as a reoperation at our institution between 2006 and 2015. Previous cardiac operations included mitral, aortic, and TV surgeries, atrial septal defect repair, and pericardiectomy. The mean age of the patients was 51.9±12.8 years, 14 (28%) were male and 35 (72%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Interestingly, Maimaiti and colleagues reported shorter bypass times in their MITS group (78.4±31.2 min) compared to the median sternotomy (90.9±22.8 min). This can be explained by the fact that all their patients had redo surgery (32). Our results showed total bypass times of 139.8±46.4 minutes.…”
Section: Operative Timesmentioning
confidence: 63%
See 4 more Smart Citations
“…Interestingly, Maimaiti and colleagues reported shorter bypass times in their MITS group (78.4±31.2 min) compared to the median sternotomy (90.9±22.8 min). This can be explained by the fact that all their patients had redo surgery (32). Our results showed total bypass times of 139.8±46.4 minutes.…”
Section: Operative Timesmentioning
confidence: 63%
“…They have reported renal failure incidence of 30.8% (52). In their comparative study, Maimaiti and colleagues reported a higher risk of acute kidney injury (AKI) in their sternotomy group reaching 35% compared to 13% in the MITS group (32). They have also reported equal incidence of new renal haemodialysis post-operatively of 13%.…”
Section: Renal Complicationsmentioning
confidence: 98%
See 3 more Smart Citations